EVALUASI PENERAPAN PSAP NO. 02 TENTANG LAPORAN REALISASI ANGGARAN DENGAN TINGKAT KESEJAHTERAAN MASYARAKAT (STUDI KASUS PADA PEMKAB JEPARA) - Subadriyah Subadriyah (Jurnal Dinamika Ekonomi & Bisnis, 2018)
PSAP.02 on the Budget Realization Report regulate reporting budget realization in the general purpose of providing information about the realization and budget reporting entities are paired. The objective of this study was to determine the suitability of preparation of budget realization in Jepara with PSAP.02 on Realized Budget Report. This study will take an object on the application of the PSAP.02 statement on the Budget Realization Report. This type of research is descriptive research. This research was conducted in Jepara government financial statements in 2014 that uses the accrual-based SAP in 2010 and 2013 that are still using SAP 2005 cash basis to the accrual. Implementation PSAP.02 for the preparation of the budget realization report indicator gained 88.9% while revenue accounting indicator is only 40% that corresponds to the PSAP.02, for the accounting indicator expenditure on the Budget Realization Report Jepara gained 53.8%, and for the accounting indicator surplus/deficit and financing the LRA Jepara of 41.7% has been applied in accordance with the PSAP.02. Welfare society is seen IPM shows an increase from 2013 of 69.11 into 69.61. Budget management professional and accountable by referring to the PSAP.02 can improve community welfare conditions Jepara as summarized in IPM Jepara.